DArTseq-based silicoDArT and SNP markers reveal the genetic diversity and population structure of Kenyan cashew (Anacardium occidentale L.) landraces - Dennis Wamalabe Mukhebi; Pauline Wambui Gachanja; Diana Jepkoech Karan; Brenda Muthoni Kamau; Pauline Wangeci King’ori; Bicko Steve Juma; Wilton Mwema Mbinda (PLoS ONE, 2025)
Cashew (Anacardium occidentale L.) is an important tree grown worldwide for its edible fruits, nuts and other products of industrial applications. The ecologically sensitive cashew-growing region in coastal Kenya is significantly affected by rising temperatures, droughts, floods, and shifting rainfall patterns. These changes adversely impact cashew growth by altering flowering patterns, increasing pests and diseases, and causing postharvest losses, which ultimately result in reduced yields and tree mortality. This is exacerbated by the long juvenile phase, high heterozygosity, lack of trait correlations, large mature plant size, and inadequate genomic resources. For the first time, the Diversity Array Technology (DArT) technology was employed to identify DArT (silicoDArT) and single nucleotide polymorphisms (SNPs) markers for genomic understanding of cashew in Kenya. Cashew leaf samples were collected in Kwale, Kilifi and Lamu counties along coastal Kenya followed by DNA extraction. The reduced libraries were sequenced using Hiseq 2500 Illumina sequencer, and the SNPs called using DarTsoft14. A total of 27,495 silicoDArT and 17,008 SNP markers were reported, of which 1340 silicoDArT and 824 SNP markers were used for analyses after screening, with > 80% call rate, > 95% reproducibility, polymorphism information content (PIC ≥  0.25) and one ratio (>0.25). The silicoDArT and SNP markers had mean PIC values ranging from 0.02–0.50 and 0.0–0.5, with an allelic richness ranging from 1.992 to 1.994 for silicoDArT and 1.862 to 1.889 for SNP markers. The observed heterozygosity and expected values ranged from 0.50–0.55 and 0.34–0.37, and 0.56–0.57 and 0.33 for both silicoDArT and SNP markers respectively. Understanding cashew genomics through the application of SilicoDArT and SNP markers is crucial for advancing cashew genomic breeding programs aimed at improving yield and nut quality, and enhancing resistance or tolerance to biotic and abiotic stresses. Our study presents an overview of the genetic diversity of cashew landraces in Kenya and demonstrates that DArT systems are a reliable tool for advancing genomic research in cashew breeding.